2018
DOI: 10.1177/0021998318792296
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of thermosetting infiltrate in powder-based composites made by additive manufacturing

Abstract: Rapid prototyping for material deposition or additive manufacturing has been widely used for short time production of parts with complex geometry in small series. The three-dimensional printing process needs post-processing to improve the strength, stiffness and/or surface finish of the parts. Printed parts in pristine condition are generally very brittle with a porous structure, so infiltrates have been introduced to improve their mechanical and physical characteristics. This work investigates the effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The authors concluded that a higher surface area under the hardened epoxy infiltrates results in increased load capacity of the sample. Lizardo et al (2019) infiltrated using epoxy polymer and cyanoacrylate under a vacuum pressure system. The samples infiltrated under vacuum with epoxy polymer achieved better mechanical strength.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors concluded that a higher surface area under the hardened epoxy infiltrates results in increased load capacity of the sample. Lizardo et al (2019) infiltrated using epoxy polymer and cyanoacrylate under a vacuum pressure system. The samples infiltrated under vacuum with epoxy polymer achieved better mechanical strength.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nowadays, various conventional manufacturing technologies for the PMCs are being replaced with the 3DP owing to the availability of the better process control and feasibility of precise positioning of the reinforcements in later. Some of the recent publications even explored the feasibility of using reinforced thermoset polymers for demanding applications . However, use of a viscous feedstock, because of the presence of the fillers, is a big challenge as such material systems often demand parametric optimizations or replacement of the certain parts, accordingly.…”
Section: Summary and Future Road Mapsmentioning
confidence: 99%
“…Some of the recent publications even explored the feasibility of using reinforced thermoset polymers for demanding applications. 129,130 However, use of a viscous feedstock, because of the presence of the fillers, is a big challenge as such material systems often demand parametric optimizations or replacement of the certain parts, accordingly. Moreover, it is difficult to conclude that whether the applications, as highlighted in the main text of the review, will receive commercialization certifications or will always be confined with the research and development laboratories.…”
Section: Summary and Future Road Mapsmentioning
confidence: 99%